The Underlying Cardiovascular Mechanisms of Resuscitation and Injury of REBOA and Partial REBOA - Stonko, David P.; Edwards, Joseph; Abdou, Hossam; Elansary, Noha N.; Lang, Eric; Savidge, Samuel G.; Hicks, Caitlin W.; Morrison, Jonathan J. (Frontiers in Physiology, 2022)
ABSTRACT Introduction: Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) is used for aortic control in hemorrhagic shock despite little quantification of its mechanism of resuscitation or cardiac injury. The goal of this study was to use pressure-volume (PV) loop analysis and direct coronary blood flow measurements to describe the physiologic changes associated with the clinical use of REBOA. Methods: Swine underwent surgical and vascular access to measure left ventricular PV loops and left coronary flow in hemorrhagic shock and subsequent placement of occlusive REBOA, partial REBOA, and no REBOA. PV loop characteristics and coronary flow are compared graphically with PV loops and coronary waveforms, and quantitatively with measures of the end systolic and end pressure volume relationship, and coronary flow parameters, with accounting for multiple comparisons. Results: Hemorrhagic shock was induced in five male swine (mean 53.6±3.6 kg) as demonstrated by reduction of stroke work (baseline: 3.1 vs. shock: 1.2 L*mmHg, p<0.01) and end systolic pressure (ESP; 109.8 vs. 59.6 mmHg, p<0.01). ESP increased with full REBOA (178.4mmHg; p<0.01), but only moderately with partial REBOA (103.0mmHg, p<0.01 compared to shock). End systolic elastance was augmented from baseline to shock (1.01 vs. 0.39 mL/mmHg, p<0.01) as well as shock compared to REBOA (4.50 mL/mmHg, p<0.01) and partial REBOA (3.22 mL/mmHg, p=0.01). Percent time in antegrade coronary flow decreased in shock (94% to 71.8%, p<0.01) but was rescued with REBOA. Peak flow increased with REBOA (271 vs. shock: 93 mL/min, p<0.01) as did total flow (peak: 2136, baseline: 424 mL/min, p<0.01). REBOA did not augment the end diastolic pressure volume relationship. Conclusions: REBOA increases afterload to facilitate resuscitation, but the penalty is supraphysiologic coronary flows and imposed increase in LV contractility to maintain cardiac output. Partial REBOA balances the increased afterload with improved aortic system compliance to prevent injury.